Pathway to Participation: The Dilemma in Early Years Education Learning Environments in Kenya - Odundo Paul Amolloh; Ganira Khavugwi Lilian (Newinera Publisher, 2022)
Listening to what children say expand upon language, building vocabulary and background knowledge in social, political and economic world for effective communication. Article 12 of the CRC 1989 stresses the right to participation in decision-making processes, which influence choices taken by children for empowering sense of belonging and community cohesion. However, too often children are denied opportunities for participation in decision-making and to exercise responsibility resulting to under democracy situations. In addition, there is limited understanding of children’s right to participate in matters affecting them in developing countries especially in Sub-Saharan Africa. The study sought to determine children’s; perceptions, preferences, interests, views and feelings concerning participation in pre-primary school learning environments in Kenya. This was an exploratory case study, which relied on data sampled from pre-primary school children and teachers in selected schools in Kenya using probability and simple random sampling techniques. Anchored on recognition theory, the study determined that participation of children is scanty and in instances where it occurs, only at the implementation stage rather than the planning design. The study recommended the need for collaboration and sharing information among children, teachers, communities and government towards realization of children’s perception to what they say and in decision making.